Bunchosia apiculata (Malpighiaceae): A new occurrence for Paraíba state, Northeastern Brazil - Sousa, Valdeci Fontes de; Francener, Augusto (Iheringia, Série Botânica., 2024)
Bunchosia apiculata Huber (Malpighiaceae): a new occurrence for Paraíba state, Northeast Brazil. Bunchosia is a Neotropical genus with about 75 species, of which 11 are known from Brazil, and one, B. pernambucana W.R. Anderson registered for Paraíba state. Here, we present the first record of B. apiculata for Paraíba, expanding its occurrence 364 km further towards the northeastern from the nearest record. This species was previously known from the states of Amapá, Pará, Ceará, Maranhão and Piauí. This paper provides a description of this species, comments on geographic distribution and habitat, photographs and conservation status. Additionally, we present a map and diagnostic key to the five species of Bunchosia from Northeast Brazil.